Synthesis of some impurities and/or degradation products of atorvastatin - Stach, Jan; Havlíček, Jaroslav; Plaček, Lukáš; Rádl, Stanislav (Collection of Czechoslovak Chemical Communications, 2008)
Synthesis of some impurities and/or degradation products of atorvastatin, calcium (3R,5R)-7- [2-(4-fluorophenyl)-5-isopropyl-3-phenyl-4-(phenylcarbamoyl)pyrrol-1-yl]-3,5-dihydroxyheptanoate, is described. These include its desfluoro analog, the corresponding (3S,5S)- and (3S,5R)-epimers, atorvastatin lactone, and some other potential impurities. The synthesized compounds as well as the corresponding intermediates were characterized by 1H NMR, 13C NMR and MS.
Keywords: statiny; financování organizované; Drug Design; Financing, Organized; Sortis; Lipitor; Heptanoic Acids; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pyrroles; racionální návrh léčiv; pyrroly; kyseliny heptylové